Who's destroying the forest a global analysis - Films For The Humanities & Sciences (Firm) (Hamilton, NJ : Films for the Humanities & Sciences, 2008)
Forest protect and nurture humanity in a variety of ways. Why, then, does deforestation continue? Who is responsible for it? This program analyzes the problem through a socioeconomic lens, drawing connections between corporate interests, food security concerns, and annihilation of the planet's woodland. Forest ecosystems and forest dwelling peoples in Asia, Africa, and South America are the main focus
DVD format
Keywords: Deforestation -- Social aspects -- Developing countries; Deforestation -- Economic aspects -- Developing countries; Deforestation -- Environmental aspects -- Developing countries